How Age and Linguistic Competence Affect Memory for Heard Information - Schneider, Bruce A.; Avivi-Reich, Meital; Leung, Caterina; Heinrich, Antje (Frontiers in Psychology, 2016)
The short-term memory performance of a group of younger adults, for whom English was a second language (young EL2 listeners), was compared to that of younger and older adults for whom English was their first language (EL1 listeners). To-be-remembered words were presented in noise and in quiet. When presented in noise, the listening situation was adjusted to insure that the likelihood of recognizing the individual words was comparable for all groups. Previous studies which used the same paradigm found memory performance of older EL1 adults on this paired-associate task to be poorer than that of their younger EL1 counterparts both in quiet and in a background of babble. The purpose of the present study was to investigate whether the less well-established semantic and linguistic skills of EL2 listeners would also lead to memory deficits even after equating for word recognition as was done for the younger and older EL1 listeners. No significant differences in memory performance were found between young EL1 and EL2 listeners after equating for word recognition, indicating that the EL2 listeners’ poorer semantic and linguistic skills had little effect on their ability to memorize and recall paired associates. This result is consistent with the hypothesis that age-related declines in memory are primarily due to age-related declines in the perceptual and attentional processes required for extracting the word pairs from a background babble of voices. Such declines are likely to increase the load on higher-order (possibly limited) cognitive processes supporting memory. The problems that these results pose for the comprehension of spoken language in these three groups are discussed.